Admissions as a facilitator of inclusion — not a gatekeeper. Issue 12 (July 2017) - Mehta, Lina; Clifford, Grace
Abstract : Although the percentage of medical students with disabilities is increasing, it continues to lag behind that of individuals with disabilities in other graduate programs. One mechanism for increasing the number of students with disabilities in medicine is through the admissions pathway. Medical school admissions is historically viewed as the gatekeeper for students with disabilities in entering the medical profession.